PERSONALITY FACTORS MORE PRONE TOWARDS DELIBERATE SELF HARM; A STUDY ON 50 PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL - Shah, Farrukh Saleem; Ghouri, Shabnum; Shah, Mubashar (Journal of Postgraduate Medical Institute, 2015)
Objective: The study is aimed to identify the personality factors of patients admitted with the history of recent deliberate self-harm (DSH). Methodology: Descriptive study with purposive sampling was carried out at Department of Psychiatry Combined Military Hospital (CMH) Lahore, Pakistan from July 2013 to January 2014. Personality profile of total 50 inpatients with DSH admitted in psychiatry department, CMH Lahore were assessed by us-ing The Sixteen Personality Factor Questionnaire. Respondents were informed and assured of the complete confidentiality of their responses. Quantitative research design was employed. The data was analyzed by using SPSS version 17. Result: Results indicated that inpatients with the history of DSH scored high on three factors i.e. Dominance (58%), Apprehension (48%) and Tension (52%). Individuals scored low on 3 factors that are reasoning (4%), Emotional stability (4%) and Liveliness (8%). Conclusion: The findings revealed some personality factors that are more consistently prominent in DSH patients. These increase vulnerability while the later considered lowering the vulnerability to DSH. The findings have thera -peutic and preventive implications.